2020
DOI: 10.1186/s13033-020-00348-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with higher levels of perceived stigma among people with schizophrenia Addis Ababa, Ethiopia

Abstract: Background: Schizophrenia is a severe and disabling chronic mental disorder and accompanied by different levels of a perceived stigma that affects almost all age groups. This perceived stigma negatively impacts the quality of life, physical, and mental well-being of people with schizophrenia. It is also linked with a poor level of functioning, poor adherence to drugs, and increased dropout rate. However, research into perceived stigma and associated factors among people with schizophrenia in low-and middle-inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…37 The result also agrees with the findings of a workshop focusing on depressed patients in the USA 10 and another study that referred to people with schizophrenia in Ethiopia, 62.6%;. 33 However, our result is lower than those of other studies conducted in Ethiopia; one of them found the prevalence of perceived stigma to be higher than that in our work 83.5%, 18 while another reported similarly higher results for epilepsy patients in Butajira, Ethiopia 81%. 38 The above differences in prevalence might be attributed to the varied timings of the studies as well as the differences in population and sample size.…”
Section: Discussionsupporting
confidence: 88%
“…37 The result also agrees with the findings of a workshop focusing on depressed patients in the USA 10 and another study that referred to people with schizophrenia in Ethiopia, 62.6%;. 33 However, our result is lower than those of other studies conducted in Ethiopia; one of them found the prevalence of perceived stigma to be higher than that in our work 83.5%, 18 while another reported similarly higher results for epilepsy patients in Butajira, Ethiopia 81%. 38 The above differences in prevalence might be attributed to the varied timings of the studies as well as the differences in population and sample size.…”
Section: Discussionsupporting
confidence: 88%
“…This significantly affects the treatment adherence, rates of relapse, ability to perform and/or enjoy occupational and social activities, future outlook, medical problems [ 2 ] [ 10 12 ]. Perceived stigma and drug non adherence were negatively affects the quality of life of patient with severe mental illness [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may contribute to noncompliance and have negative impact on the patient [6]. Stigmatization, lack of motivation, and social withdrawal are other factors that reduce quality of life and self esteem in schizophrenia [7].…”
Section: Introductionmentioning
confidence: 99%